2016
DOI: 10.1128/aac.00026-16
|View full text |Cite
|
Sign up to set email alerts
|

SpoVG Regulates Cell Wall Metabolism and Oxacillin Resistance in Methicillin-Resistant Staphylococcus aureus Strain N315

Abstract: bIncreasing cases of infections caused by methicillin-resistant Staphylococcus aureus (MRSA) strains in healthy individuals have raised concerns worldwide. MRSA strains are resistant to almost the entire family of ␤-lactam antibiotics due to the acquisition of an extra penicillin-binding protein, PBP2a. Studies have shown that spoVG is involved in oxacillin resistance, while the regulatory mechanism remains elusive. In this study, we have found that SpoVG plays a positive role in oxacillin resistance through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The SigB transcription factor is related to the expression of high-level methicillin resistance and regulated in response to growth phase and environmental stress (38,39). Moreover, spoVG, a SigB-controlled protein, is a critical factor that impacts cell wall synthesis, and it is likewise involved in antibiotic resistance and virulence (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The SigB transcription factor is related to the expression of high-level methicillin resistance and regulated in response to growth phase and environmental stress (38,39). Moreover, spoVG, a SigB-controlled protein, is a critical factor that impacts cell wall synthesis, and it is likewise involved in antibiotic resistance and virulence (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…WTAs play a crucial role in septal localization of autolysins in S. aureus cells and interact with them, thereby regulating autolysis (4,19,20,43,55,56). WTAs are also known to have an important role in peptidoglycan cross-linking, as well as in ␤-lactam and vancomycin resistance, determining septal localization of PBP4 and FmtA (9-11, 16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings suggest that the extra murein hydrolase bands in zymogram analysis produced by the msaABCR mutants in both VISA and MRSA strains were due to increased AtlA production as well as increased processing of AtlA and/or other murein hydrolases by the increased activity of proteases. Therefore, increased protease- Previous studies have shown that WTAs are cell-surface glycopolymers that are covalently attached to peptidoglycan and modulate AtlA murein hydrolase activity as well as its localization (19,43). In addition, WTAs are also known to play a role in PBP4 localization, lysozyme resistance, and cell wall cross-linking (10,11,31).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to successfully synthesize graphene flakes with and without the enhancement of a magnetic field. 25,26,27,28,29,30,31 Graphene was synthesized using anodic arc ablation in a helium environment at atmospheric pressure. Samples were collected from the chamber wall or the surface of the magnet, and were characterized with SEM, TEM, AFM and RAMAN spectroscope.…”
Section: Introductionmentioning
confidence: 99%